Disinfection and hand hygiene knowledge, attitude, and practices among childcare facilities staff during the COVID-19 pandemic in Anhui, China: a cross-sectional study - Chen, Fang; Xu, Qing Hua (Frontiers in Public Health, 2024)
Objective To investigate the disinfection and hand hygiene knowledge, attitude and practice (KAP) and associated influencing factors among childcare facilities staff during the COVID-19 pandemic in Anhui, and provide information for developing disinfection and hand hygiene strategies for childcare facilities.Methods A web-based cross-sectional study was conducted among Anhui province in China in September 2020. 60 childcare facilities in 2 cities of Anhui Province were selected using the convenient sampling method for questionnaires. The questionnaires were distributed through a webbased platform. The disinfection and hand hygiene knowledge scores among childcare facilities staff were calculated and its influencing factors were analyzed. The accuracy rates of knowledge and attitude, the practice rates of behavior were calculated and analyzed.Results A total of 1029 participants were included in the study. The score of disinfection and hand hygiene knowledge was 21.19±2.32, with urban areas scoring higher than rural areas. The higher the education level and more years worked, the higher the scores. The scores of staff with training or supervision were higher than those without training or supervision. The lowest knowledge accuracy rate (46.3%), lowest attitude accuracy rate (4.2%), and "always" practice rate (5.3%) of childcare facility staff were all regarding the question categories of usable range of disinfectants. The accuracy rates of hand hygiene knowledge and attitude among the childcare facility staff were high (83.7%-99.6%), but the "always" practice rate was in the middle range (63.0%).The disinfection and hand hygiene knowledge among childcare facilities staff was incomplete during the COVID-19 pandemic in Anhui. It is necessary to continuously implement education and training, especially in rural areas, there should be monitoring system for the usage, effect and adverse reaction in China, interventions should be tried to increase the hand hygiene practices compliance. Further research should be considered on the training and intervention of disinfection and hand hygiene, the safety of disinfection measures and more operational hand hygiene methods in childcare facilities.